Clinical evaluation of keratometry and computerised videokeratography: intraobserver and interobserver variability on normal and astigmatic corneas. Issue 6 (1st June 1998) - Karabatsas, Constantinos H; Cook, Stuart D; Papaefthymiou, John; Turner, Phil; Sparrow, John M
Abstract : AIMS: To evaluate intra- and interobserver variability in measurements on normal and astigmatic corneas with keratometry and computerised videokeratography. METHODS: Keratometric readings with the 10 SL/O Zeiss keratometer and topographic maps with the TMS-1 were obtained by two independent examiners on 32 normal and 33 postkeratoplasty corneas. Inter- and intraobserver coefficients of variability (COR) for measurements of steep and flat meridian power and location, in addition to the magnitude of astigmatism, were assessed. RESULTS: Compared with TMS-1, the 10 SL/O keratometer showed a superior repeatability in measuring normal corneas (intraobserver COR for keratometry and TMS-1 respectively: 0.22 and 0.30 D for steep meridian power; 0.18 and 0.44 D for flat meridian power; 0.26 and 0.40 D for astigmatism; 5° and 26° for steep meridian location; 5° and 13° for flat meridian location). Astigmatism intraobserver COR (0.20 D and 0.26 D for the two observers) and interobserver COR (0.28 D) of the keratometer for normal corneas was very good and not affected by observers' experience. Repeatability of the TMS-1 on normal corneas was found to be: (a) observer related, and (b) astigmatism related. A novice observer showed a much greater COR (1.62 D for astigmatism, 30° for flat meridian location) compared with the experienced examiner (0.40 D for astigmatism, 13° for flat meridian location). Higher deviation scores were observed for corneas with higher astigmatism. For the postkeratoplasty corneas, again the keratometer achieved superior reproducibility (astigmatism interobserver COR 1.12 D for keratometry, 4.06 D for TMS-1; steep meridian location interobserver COR 10° for keratometry, 34° for TMS-1). CONCLUSION: Keratometric readings are more reproducible than topographic data both for normal and postkeratoplasty corneas. The two instruments should not be used interchangeably especially on highly astigmatic corneas. For the TMS-1, users with the same level of experience should be employed in clinical or experimental studies.